Impact of Land Surface Run Off On The Water Quality At Batam Mariculture Area - Sachoemar, Suhendar I. (Jurnal Hidrosfir Indonesia, 2007)
An impact of the land surface run off on the water quality was observed at Batam Mariculture Estate during the flood tide of the Southeast Monsoon. The existing of land surface run off was significantly identified on the increasing of the turbidity as well as total suspended solid (TSS) concentration in the nearby of the upper eastern part of the shoreline and it spread up to the southern part driven by surface current. As consequence, the water quality was degraded, particularly on the water transparency. The land surface run off was also increasing the phosphate concentration that stimulated and promoted on the increasing of the chlorophyll-a and dissolve oxygen (DO). But the nitrogen compound (nitrate and nitrite), and silicate were not affected.Keywords: Land surface run off, water quality, Batam Mariculture Estate